Development of the Konsep MI in word classification - Fuzzy Delphi Analysis (FDM) based on expert consensus - Nagaraju, Pavitira; Subramaniam, Vijayaletchumy (Human Resources Management Academic Research Society (HRMARS), 2024)
Determining word classes such as nouns, verbs, and adjectives in Malay language remains a challenge for non-native students especially at Sekolah Jenis Kebangsaan Tamil (SJKT). Therefore, the Konsep MI, which emphasizes two criteria such as meaning of the word and presence of affixes has been developed to facilitate the process of word class identification. Hence, this study was conducted to obtain expert consensus on the design and development of the Konsep MI, which includes Word Class Signal Lights, Orang Adjektif, Pyramid NAsKp Model, and Cam Kata game, to meet the needs of the target group. The Fuzzy Delphi Method (FDM), assisted by a questionnaire using a five-point Likert scale was employed to gather expert opinions. Data analysis was based on the views of 20 experts in the field of Malay language regarding the design and development of the concept before implementation in schools. The findings indicated that all presented items met acceptance criteria, with threshold values (d) below 0.2, expert consensus exceeding 75%, and defuzzification values exceeding 0.5. All suggestions for improvement proposed by experts were considered and accepted to ensure that the incorporated elements enable students to understand the process of word class identification easily. Therefore, the development of the Konsep MI has been endorsed by experts as a guide to help students learn about word class identification through an educational and entertaining approach, aligned with 21st-century learning principles.